2021
DOI: 10.1002/lno.12005
|View full text |Cite
|
Sign up to set email alerts
|

Temporal declines in Wadden Sea phytoplankton cell volumes observed within and across species

Abstract: Cell size is a master trait in the functional ecology of phytoplankton correlating with numerous morphological, physiological, and life-cycle characteristics of species that constrain their nutrient use, growth, and edibility. In contrast to well-known spatial patterns in cell size at macroecological scales or temporal changes in experimental contexts, few data sets allow testing temporal changes in cell sizes within ecosystems. To analyze the temporal changes of intraspecific and community-wide cell size, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 88 publications
3
3
0
Order By: Relevance
“…As hypothesized, we observed a reduction in cell size with rising temperature, which aligns with numerous prior studies demonstrating a decline in cell size under elevated temperatures in phytoplankton communities (e.g., Hillebrand, Di Carvalho, et al., 2022 ; Peter & Sommer, 2013 ; Yvon‐Durocher et al., 2011 ; Zohary et al., 2021 ) and single species (Bernhardt et al., 2018 ; Hofmann et al., 2019 ). Our data thus support the suggestion made by Daufresne et al.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As hypothesized, we observed a reduction in cell size with rising temperature, which aligns with numerous prior studies demonstrating a decline in cell size under elevated temperatures in phytoplankton communities (e.g., Hillebrand, Di Carvalho, et al., 2022 ; Peter & Sommer, 2013 ; Yvon‐Durocher et al., 2011 ; Zohary et al., 2021 ) and single species (Bernhardt et al., 2018 ; Hofmann et al., 2019 ). Our data thus support the suggestion made by Daufresne et al.…”
Section: Discussionsupporting
confidence: 91%
“…Cell size is a master trait that is coupled with resource uptake and utilization strategies (Hillebrand, Acevedo‐Trejos, et al., 2022 ; Litchman & Klausmeier, 2008 ), and is therefore influenced by the availability of resources. Consequently, higher light intensity and nutrient concentration increase phytoplankton cell size at both, individual species level (Falkowski & Laroche, 1991 ; Hessen et al., 2002 ; Thompson et al., 1991 ) and community mean cell size level (Hillebrand, Di Carvalho, et al., 2022 for phosphorus effect, Peter & Sommer, 2013 ). Moreover, much attention has been given to the temperature dependence of phytoplankton cell size (Zohary et al., 2021 ) as cell size reduction is proposed to be the third universal response to climate warming (Daufresne et al., 2009 ) and thus directly linked to shifts in consumer size structure (Sommer et al., 2017 ; Venkataramana et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Environmental factors can influence phytoplankton F v / F m and cell size. This study demonstrated that nitrate limitation resulted in a significant decrease of F v / F m and cell size ( Figure 4C ), and other studies also reported that nutrient availability and warming can trigger a change of phytoplankton cell size ( Maranon et al, 2013 ; Hillebrand et al, 2022a , b ). In addition, environmental stress such as ultraviolet radiation and heavy metals can affect F v / F m by damaging the structure and metabolism of pigment-protein complexes in phytoplankton cells ( Kolber et al, 1994 ; Beecraft et al, 2019 ), and in a response, the F v / F m and cell size are both changed ( Tan et al, 2019 ; Hillebrand et al, 2022a ).…”
Section: Discussionsupporting
confidence: 78%
“…Phytoplankton cell size, varying widely from less than 1 to 10 9 μm 3 ( Beardall et al, 2009 ), is well known as an essential functional trait determining the performance at species and community levels ( Maranon, 2015 ; Hillebrand et al, 2022a ). As such, phytoplankton cell size has an allometric relationship with the functional performance, including cellular rates of carbon fixation, respiration, and exudation as well as resource uptake and content ( Maranon et al, 2013 ; Hillebrand et al, 2022b ). On the other hand, phytoplankton cell size can be influenced by grazing and environmental stress such as nutrient limitation and warming ( Kiørboe, 1993 ; Maranon et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Zooplankton feeds on phytoplankton. They are accountable for eating millions of little algae and other phytoplankton [3,4]. Phytoplankton not only serves as nutrition or food or diet for the aquatic animal, but also plays a significant role in keeping the biological equilibrium and the quality of water [5].…”
Section: Introductionmentioning
confidence: 99%